Perceptions of the School of Library and Information Studies students and alumni on archives and records management electives - Llabore, Jenny Rose S. (2012)
Library and Information Science Education in the University of the Philippines has four major tracks that students can choose on which to specialize. These are the core tracks wherein the field is honing the skills for the future librarians of the nation.